Breastfeeding Practices in Morocco (1992-2025): Multicentric Analysis of National Surveys, Meta-Analysis, and Exploration of Key Indicators - El Mossaoui, Mohamed; Barkat, Amina (International Journal of Child Health and Nutrition, 2025)
Introduction: Breastfeeding is a cornerstone of infant nutrition, playing a crucial role in neonatal health, growth, and maternal-infant bonding. Despite WHO recommendations advocating exclusive breastfeeding for the first six months, breastfeeding practices in Morocco remain suboptimal, with disparities in both initiation and continuation. This study aims to analyze the epidemiology of breastfeeding in Morocco, assess maternal knowledge, and evaluate the effectiveness of national promotion programs while forecasting breastfeeding trends for 2025. Materiel and Methods: A systematic review and meta-analysis were conducted, synthesizing data from 1992 to 2025 across databases including PubMed, ScienceDirect, Scopus, and Google Scholar. National surveys (ENPSF, PAPCHILD) and epidemiological studies were analyzed to determine the prevalence, trends, and determinants of breastfeeding. A linear regression model was applied to estimate the relationship between early breastfeeding initiation and exclusive breastfeeding at six months, with statistical significance assessed using Pearson correlation and p-value analysis. Projections for 2025 were made using predictive epidemiological modeling. Results: The early breastfeeding rate in Morocco remains inconsistent, with significant regional variations and socio-economic disparities. Exclusive breastfeeding rates remain below WHO recommendations, with a projected stagnation at 40.6% by 2025. The correlation between early and exclusive breastfeeding at six months is weak (r=0.36, p=0.759), indicating that additional determinants influence breastfeeding duration. Despite national awareness efforts, maternal knowledge gaps persist, contributing to premature breastfeeding cessation and early introduction of complementary feeding. Discussion: The findings highlight structural and behavioral barriers to sustained breastfeeding, including limited postpartum support, workplace constraints, and aggressive infant formula marketing. The current focus on early breastfeeding promotion may be insufficient to improve exclusive breastfeeding rates. Strengthening maternity leave policies, healthcare professional training, and postpartum follow-up strategies is essential to prevent stagnation in breastfeeding rates. Conclusion: This study underscores the urgent need for comprehensive breastfeeding promotion policies in Morocco, extending beyond initiation efforts to focus on long-term adherence to exclusive breastfeeding. Strengthening healthcare interventions, workplace accommodations, and maternal education programs is essential to achieving WHO’s recommended breastfeeding targets and improving infant health outcomes. Impact and Contribution: This study provides a robust assessment of breastfeeding practices in Morocco by combining epidemiological modeling, national survey data, and predictive analysis. The findings support public health strategies to increase breastfeeding rates, reduce disparities, and enhance maternal and infant nutrition.